1995
DOI: 10.2337/diab.44.7.845
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of β-Cell Sensitivity From Intravenous Glucose Tolerance Test C-Peptide Data: Knowledge of the Kinetics Avoids Errors in Modeling the Secretion

Abstract: Parametric models of insulin secretion are used to measure indexes of beta-cell function from plasma C-peptide concentration during an intravenous glucose tolerance test (IVGTT). Since the models have been usually assessed against plasma C-peptide data, both secretory and kinetic parameters need to be simultaneously estimated. However, undesired compensations between the two sets of parameters may arise. In this study, in order to evaluate IVGTT insulin secretion models, we have analyzed IVGTT data from seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 22 publications
3
74
0
Order By: Relevance
“…In a standard IVGTT analysed with minimal models, sampling is prolonged until 180-240 min, and glucose thresholds and basal insulin secretion rates are based on the levels attained at the end of the test [13,14]. Thus, glucose threshold and basal insulin secretion in the minimal model analysis of the IVGTTs included in the present study were higher than they might have been if sampling had been continued for an additional 120-180 min.…”
Section: Modelmentioning
confidence: 91%
See 3 more Smart Citations
“…In a standard IVGTT analysed with minimal models, sampling is prolonged until 180-240 min, and glucose thresholds and basal insulin secretion rates are based on the levels attained at the end of the test [13,14]. Thus, glucose threshold and basal insulin secretion in the minimal model analysis of the IVGTTs included in the present study were higher than they might have been if sampling had been continued for an additional 120-180 min.…”
Section: Modelmentioning
confidence: 91%
“…This model is similar to the one proposed by us for C-peptide during hyperglycaemic clamp [11], which, in turn, was based primarily on the minimal model introduced by Toffolo et al for C-peptide during IVGTT [13] (described in the Appendix). Both readily releasable insulin (RRI; the first peaking phase of insulin secretion during IVGTT; pmol·l −1 ) and sigma (beta cell sensitivity to glucose during the second phase of insulin secretion;…”
Section: Subjectsmentioning
confidence: 98%
See 2 more Smart Citations
“…Minimal models are useful tools for the study of IVGTT data by estimating parameters from model fitting to the observed data [3][4][5], and can provide a fuller picture of b-cell function than the AIR index, in particular when based on C-peptide measurements [5,6]. These models must be fairly simple to allow parameter identification, but should at the same time reflect truthfully the underlying biology down to the cellular events underlying insulin secretion.…”
Section: Introductionmentioning
confidence: 99%